THE PERSPECTIVE OF ISLAMIC PHILOSOPHY, SUFISM, ISLAMIC JURISPRUDENCE AND JAVANESE TRADITION ON WOMEN - Achmad Khudori Soleh; Erik Sabti Rahmawati; Humaida Ghevira Syavia Camila; Ahmad Hidayat Buang (ULUL ALBAB Jurnal Studi Islam, 2023)
Islamic philosophy, Sufism, Islamic jurisprudence and Javanese traditions have their views on women. Some regard women as subordinate to men, some groups position women as equal to men, and others accept women as male leaders. This study aims to analyse the views of Islamic philosophy, Sufism, Islamic jurisprudence and Javanese traditions on women. This study is a literature review using qualitative methods. The data source was taken from the literature using primary sources as the main reference. The results indicated that Islamic philosophy represented by al-Fârâbî (870-950) and Sufism by Ibn Arabi (1165-1240) placed women in an equal position with men. Nevertheless, Islamic jurisprudence studies tend to place women below men. Meanwhile, the Javanese tradition encapsulates both views. On the one hand, the Javanese tradition places women as an important part of men, but on the other hand, it places women as men's assets. However, the Javanese tradition can accept women's leadership over men. Regarding this, this study recommends that Islamic philosophy and Sufism's perspectives on women should be socialized more to strengthen a balanced view of the relationship between women and men.